Pengaruh Penggunaan Metode Jigsaw Terhadap Peningkatan Motivasi Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam - Apri Sulistia; Moh Sobirin (La-Tahzan: Jurnal Pendidikan Islam, 2022)
The motivation to learn Islamic Religious Education at SMP Negeri 2 Slawi is still low, this is due to the lack of variations in learning methods, where learning is still Teacher Centered (teacher-centered) so that students experience boredom. Therefore, a learning model is needed that can activate student motivation, one of which is by using the jigsaw method. this learning method is more effective and can increase student motivation. This research method is a pre Experimental design method with One Group Pretest and Posttest design type. Data collection in this study was in the form of questionnaires or questionnaires and documentation. Student motivation is measured using a questionnaire-shaped test of 20 statements that have been declared valid and reliable. The result of this study is the use of the jigsaw method can affect the learning motivation of students in class VIII at SMP Negeri 2 Slawi. Based on the calculation of the t-test that has been carried out on the pretest value and the posttest value, the tcount obtained a value of 15.052 and the ttable is 1.67 so that the result is tcount> ttable which means Ha is accepted and Ho is rejected. So, it can be concluded that there is an effect of the jigsaw method on increasing learning motivation in Islamic Religious Education class VIII at SMP Negeri 2 Slawi. The indicators that influence the increase in student learning motivation using the jigsaw method are the desire and desire to succeed, the encouragement and needs in learning, the hopes and ideals, the interesting activities in learning, and the conducive learning environment.